Carbonatação acelerada em fibrocimentos compostos de resíduos de quartzito e fibras UKP - Terra, Isabelle Cristine de Carvalho (2023)
The objective was to investigate the use of residues from the pulping of unbleached kraft pulp (UKP) and quartzite mining, as well as the use of the accelerated carbonation (AC) technique and the addition of air-entraining surfactants. Two stages were carried out, the first with 4 initial treatments, which were the control without AC and the others with different periods of AC of 6, 9 and 12 hours. After carrying out the first stage, 3 treatments were produced, the control and the others with the addition of drycast and Darafill air-entraining surfactant additives, verifying those with and without CA for 9 hours. Fiber cements were characterized according to the physical properties of apparent density (AD), water absorption (AA), apparent porosity (PA) and the mechanical properties of modulus of rupture (MOR), modulus of elasticity (MOE), limit of proportionality (LOP ) and toughness. Thermogravimetry (TG) analyzes were approached in order to monitor the formation of carbonates throughout the accelerated carbonation process and scanning electron microscopy (SEM) to verify the interaction between the constituent materials. As a result of the first stage, there was no significant effect on AD, PA and AA in the fiber cements in relation to the different AC times. There was a tendency for the MOR, MOE and LOP values to decrease as the periods subject to CA increased. There was a significant improvement in the tenacity properties of the fiber cements subjected to longer periods of CA, with a tendency for this property to stabilize between 9 am and 12 pm. Regarding the TG and DTG analyses, it was possible to verify that there was the formation of calcium carbonate due to the CA process, leading to a decrease in the alkalinity of the matrix, which provided a less aggressive environment for the UKP fibers. In this way, it was concluded that the best CA time was 9 hours, being the viable technique to improve the interaction between the matrix and the fiber. Regarding the results of the second stage, the fiber cements with the Drycast additive obtained an increase in the results of AA and PA, and a decrease in DA. They did not show differences in the results of MOR, MOE and LOP, and there was a decrease in toughness. As for the fiber cements with Darafill, there was a decrease in the results of AA and PA with the increase in DA. For the MOE and LOP mechanical properties, no difference was observed in relation to the control. However, there was an increase in toughness and MOR. Regarding AC, there was an increase in the results of MOR, MOE and LOP with the use of the technique, as well as there was no significant interaction between surfactants and AC in the studied fiber cements. In this way, the use of additives is concluded, in the case of Drycast, it enabled the reduction of density and, Darafill, improved the mechanical properties MOR and Tenacity.